Implementation of Good Governance Principles in Improving Public Services : A Case Study of the Ministry of Education and Culture - Wahidin Septa Zahran; Airi Terada; Jiraporn Saengsroi (Yayasan Ilomata, 2023)
Good governance in Indonesia has started to be implemented since the outbreak of the reform era. Good Governance is one of the reform tools that is absolutely applied in a new government. However, if you look at the development of reforms that have been going on for quite a long time, the implementation of good governance in Indonesia cannot be said to be fully successful in accordance with the aspirations of the previous reforms. The occurrence of a national crisis and various problems in Indonesia were partly caused by weaknesses in government management, especially the bureaucracy which did not heed the principles of good governance. As a result, various problems arise, such as the deteriorating quality of service to the community. This is a qualitative research with a case study approach. Data collection was carried out using semi-structured interviews with 20 applicants who are managers of training institutions and community learning centers (CLC). The results of this study indicate that the implementation of good governance in the Ministry of Education and Culture still has to be improved and this will affect the public services they apply, particularly in 4 aspects namely participation, transparency, responsiveness and equity.